139k views
4 votes
Tan^2theta - Sin^2theta = tan^2theta. sin^2theta
explain this step


Tan^2theta - Sin^2theta = tan^2theta. sin^2theta explain this step ​-example-1
User Msigman
by
5.1k points

1 Answer

5 votes

tan²(θ) - sin²(θ) = sin²(θ)/cos²(θ) - sin²(θ)

-- because tan(θ) = sin(θ)/cos(θ) by definition of tangent --

… = sin²(θ) (1/cos²(θ) - 1)

-- we pull out the common factor of sin²(θ) from both terms --

… = sin²(θ) (1/cos²(θ) - cos²(θ)/cos²(θ))

-- because x/x = 1 (so long as x ≠ 0) --

… = sin²(θ) ((1 - cos²(θ))/cos²(θ))

-- we simply combine the fractions, which we can do because of the common denominator of cos²(θ) --

… = sin²(θ) (sin²(θ)/cos²(θ))

-- due to the Pythagorean identity, sin²(θ) + cos²(θ) = 1 --

… = sin²(θ) tan²(θ)

-- again, by definition of tan(θ) --

User Prince Hernandez
by
4.6k points